Effect of Coconut Water on Weight Loss and Physiological Responses of Sheep after Short-Distance Transportation - Yulianti, K. D.; M. Baihaqi; S. Rahayu (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
Transportation can cause stress, which leads to changes in body weight and physiological responses. Coconut water can reduce oxidative stress and improve the physiological response of sheep, as well as maintain hydration and metabolism to prevent weight loss. This study aims to analyze changes in body weight and physiological responses in thin-tailed Sheep given coconut water-based electrolyte solution. A total of 20 male thin-tailed Sheep with an average weight of 21.47 ± 1.47 kg were used in this study. The study used a Completely Randomized Design (CRD) with four treatments and five replications: P0 = control (400 ml of water), P1 = 100 ml of coconut water + 300 ml of water, P2 = 200 ml of coconut water + 200 ml of water, and P3 = 300 ml of coconut water + 100 ml of water. Data were analyzed using ANOVA, followed by Duncan’s test. The results showed that the administration of coconut water to thin-tailed Sheep had no significant effect (P > 0.05) on rectal temperature, but had a significant effect (P < 0.05) on body weight loss, heart rate, and respiratory rate. The administration of coconut water to thin-tailed Sheep before transportation can reduce stress and body weight loss after transportation.